Przestrzeń informacyjna tekstów prasowych w dobie kultury masowej - Bednarek, Zbigniew (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2010)
The article is attempt to answer a question, what is “information space”, how this appearance functioned at media and what decided about border. Text is analysis of relations which occurred in “information space” and ways exist of journalism in mass culture.